Urban squatting with rent-seeking organizers - Jan K. Brueckner (Center for Economic Studies and ifo Institute (CESifo), 2012)
This paper extends a new line of research on urban squatting that focuses on the role of the squatter organizer. The model replaces the benevolent organizer from previous studies with a collection of competing, rent-seeking squatter organizers, a structure that may offer a realistic picture of many cities in less-developed countries. In addition to delineating the structure of such a competitive model, the analysis generates a host of comparative-static results and other insights. Among other things, the analysis shows that competition among squatter organizers has much in common with competition in a traditional industry setting.
Keywords: R20; R30; 330; squatting; rent-seeking; urbanization; Randgruppe; Urbanisierung; Rent Seeking; Theorie